Influence of six substrates in Pinus ponderosa grown in containers under greenhouse conditions - Olivo, Verónica B.; Buduba, Carlos G. (Bosque (Valdivia), 2006)
The influence of six substrates on Pinus ponderosa grown was studied in containers under greenhouse conditions. Treatments used were elaborated in a 1:1 proportion with an organic (coco fiber or Sphagnum peat moss) and an inorganic (pumice, vermiculite or perlite) compound. Different morphologic features were measured eight months later. The plants developed on vermiculite showed the best results. The combination of vermiculite with peat moss presented the greater size for all studied variables: stem diameter (4.9 cm), shoot height (25.4 cm), wet and dry weight of the whole plant (20.9 and 5.7 g), dry weight of the aerial and root portion (3.5 and 2.1 g), dry weight of the main root (0.7 g) and dry weigh of secondary roots (1.5 g). Three indexes were also evaluated in order to determine the plant quality. The substrates with vermiculite presented the best behavior for the different indexes.